2021
DOI: 10.1038/s41598-021-89175-7
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent X chromosome inactivation and upregulation during non-human primate preimplantation development revealed by single-cell RNA-sequencing

Abstract: In mammals, dosage compensation of X-linked gene expression between males and females is achieved by inactivation of a single X chromosome in females, while upregulation of the single active X in males and females leads to X:autosome dosage balance. Studies in human embryos revealed that random X chromosome inactivation starts at the preimplantation stage and is not complete by day 12 of development. Alternatively, others proposed that dosage compensation in human preimplantation embryos is achieved by dampeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The expression of KCNQ1OT1, which is also involved in DNA methylation, is also reported to be signi cantly reduced in vitri ed oocytes [33], suggesting KCNQ1OT1 may be involved in the regulation of ovarian function. Using scRNA-seq data from preimplantation embryos, Cidral et al [34] demonstrated that XIST is upregulated at the morula stage and that its expression is higher in female embryos than in male embryos. Moreover, we nd that the DEGs identi ed in granulosa cells 6 from old individuals and POI patients when compared with the normal group, were all enriched in the phagosome and antigen processing and presentation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of KCNQ1OT1, which is also involved in DNA methylation, is also reported to be signi cantly reduced in vitri ed oocytes [33], suggesting KCNQ1OT1 may be involved in the regulation of ovarian function. Using scRNA-seq data from preimplantation embryos, Cidral et al [34] demonstrated that XIST is upregulated at the morula stage and that its expression is higher in female embryos than in male embryos. Moreover, we nd that the DEGs identi ed in granulosa cells 6 from old individuals and POI patients when compared with the normal group, were all enriched in the phagosome and antigen processing and presentation pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to XCI, both sexes upregulate the remaining active X chromosome (Xa), in a process known as X chromosome upregulation (XCU), which resolves dosage imbalance between the sole Xa and diploid autosomal gene expression [15][16][17][18][19][20][21]. XCU has been reported in several placental mammals including mice [18,22], marmosets (non-human primates) [23], and humans [18], and in nonplacental mammals such as marsupials [14]. Despite advances, the molecular processes underlying the evolution of XCU in mammals remain unclear.…”
Section: Introductionmentioning
confidence: 99%